Automated high-throughput activity and stability screening of electrocatalysts - Jenewein, Ken; Akkoc, Gun D.; Kormányos, Attila; Cherevko, Serhiy (Chem Catalysis, 2022)
Common high-throughput (HT) approaches rapidly assess the activity of electrocatalyst libraries toward electrochemical conversion reactions. The short time regime on which individual measurements are performed creates a false perception of catalyst durability, masking the true catalyst performance by the omission of detailed stability assessments during HT campaigns. Here, an automated scanning flow cell coupled to an inductively coupled plasma mass spectrometer was developed, allowing a simultaneous HT determination of the catalyst activity and stability. Fe-Ni and Fe-Ni-Co oxide libraries were automatically synthesized by a custom-programmed pipetting robot and examined as an oxygen evolution catalyst in neutral media, the advancement of which remains a great challenge. Ni-rich compositions in Fe-Ni oxides show higher activity but also significant catalyst loss due to the major Ni dissolution, which triggers Fe dissolution. Co-rich compositions in Fe-Ni-Co oxides attain the best synergy between activity and stability.
CRIS-Team Scopus Importer:2022-11-04
Keywords: automation; high-throughput; ICP-MS; in situ stability; liquid-handling robot; oxygen evolution; scanning flow cell; SDG7: Affordable and clean energy; transition metal oxides